Serum suppression of tumorigenicity 2 level is an independent predictor of all-cause mortality in HIV-infected patients. (13th November 2017) - Thiébaut, Rodolphe; Hue, Sophie; Le Marec, Fabien; Lelièvre, Jean-Daniel; Dupon, Michel; Foucat, Emile; Lazaro, Estibaliz; Dabis, François; Duffau, Pierre; Wittkop, Linda; Surenaud, Mathieu; Pellegrin, Isabelle; et al.
Abstract : Objective: To evaluate the predictive value of soluble suppression of tumorigenicity 2 (sST2), a decoy receptor of IL-33 involved in several inflammatory and immune diseases, for death in HIV infection. Design: Patients enrolled in the ANRS CO3 Aquitaine Cohort, a prospective hospital-based cohort of HIV-1-infected patients, who had a plasma sample available in the biobank were systematically eligible. Methods: sST2, soluble CD14 (sCD14) and IL-6 were measured using Luminex multiplex bead-based technology (R&D Systems) and a Bio-Plex 200 instrument (BioRad). Predictive capacities of sST2, sCD14, IL-6 and of the Veterans Aging Cohort Study clinical score at baseline on overall mortality were compared using multivariable Cox proportional hazards models. Results: During a median follow-up of 7.2 years [interquartile range (IQR): 6.0; 7.9], 93 deaths from all causes (incidence rate 9.9 per 1000 patient-years; 95% confidence interval 7.9–11.9) were reported in 1414 patients. The median sST2 baseline concentration was 22.9 ng/ml (IQR: 17.7; 30.3) and was higher (30.8 ng/ml, IQR: 21.5; 42.1) in patients who died as compared with those who stayed alive (22.6 ng/ml; IQR: 17.5; 29.6) ( P  < 10 −4 ). An increased risk of death of 21% for a concentration 10.0 ng/ml higher of sST2 remained after adjustment for sCD14, IL-6 and Veterans Aging Cohort Study score (adjusted hazard ratio: 1.21; P  < 10 −4 ). The predictive capacity of sST2 was confirmed in a validation cohort ( n  = 386, 31 deaths) with an improved area c -index from 0.804 without sST2 to 0.811 with sST2. Conclusion: sST2 is a new valuable biomarker to evaluate the risk of all-cause mortality in HIV disease. Abstract : Supplemental Digital Content is available in the text